EVALUATING TECHNOLOGY-BASED DRUG INVENTORY FRAMEWORK IN HOSPITALS VIA COBIT 2019 AND REGULATIONS - Wulandari, Mei -; Putra, Yuniarti Hidayah Suyoso (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Globalization has accelerated technological advancements, intensifying competition in business and industry. In healthcare, effective management of medical supplies, particularly through information systems, is crucial. This study evaluates the strengths, weaknesses, and challenges of drug inventory management at RSI Aminah Blitar, focusing on data accuracy, operational efficiency, and regulatory compliance in implementing a computerized Accounting Information System (AIS). The research employs a qualitative case study approach, analyzing both computerized (Khanza Application) and manual (stock cards) systems. Data was collected through direct observation, interviews with key personnel (Pharmacy Head, Logistics, and Finance), and document analysis. Framed by COBIT 2019 and hospital regulations, the findings highlight significant improvements in accuracy and efficiency through computerization. However, challenges persist, including manual-computerized system synchronization, human resource limitations, delivery delays, and invoice discrepancies. RSI Aminah Blitar aims to enhance integration and collaboration with IT to optimize drug inventory management and regulatory compliance.